STUDY OF THE APPLICATION OF THE ZERO DELTA RUN-OFF CONCEPT TO THE WATER RESOURCE MANAGEMENT SYSTEM OF ISLAND RECLAMATION, GOLF ISLAND PANTAI INDAH KAPUK (PIK) - Zatalini, Rivia
As the nation's capital, DKI Jakarta continues to experience rapid population growth, as a result of population growth is the need for development in the form of facilities and infrastructure, one of which is the need for housing. However currently the need for space for settlements and facilities in DKI Jakarta is very limited, the government has permitted to build of a reclamation area in Jakarta Bay. One of the reclamation islands being built for residential and commercial areas is the Golf Island Pantai Indah Kapuk area. Based on the master plan of the Jakarta Bay reclamation plan, the Golf Island area is located on Island D. The area of the Golf Island reclamation island is 303 Ha. Rainwater management and drainage systems are carried out in a closed manner using a polder system. With the application of the polder system, rainwater will be discharged into the sea and is less utilized. In an island area, of course, there is no source of fresh water other than rainwater, therefore a rainwater management system is needed. This study is intended to analyze rain as a source of water that can be harvested as a source of clean water and compare it with the need for clean water in the Golf Island PIK area. While the purpose of this study is to analyze rainwater management in the Golf Island PIK area based on the concept of water balance by applying the concept of zero delta run-off based on engineering planning of drainage systems and polders. The study method includes analysis of hydrological and hydraulic data which were analyzed using primary and secondary data collected. The primary data collected directly by the researcher is the measurement of the reservoir and water sampling. Secondary data such as rainfall data, site plans, and drainage network maps were obtained from related agencies. The zero delta run-off mathematical model used is ?Q = Q runoff – Q Catchment Area = Not 0 (zero) = Maintenance Flow (baseflow). The results of the analysis show that with a roof area of 536.036 m2 and a surface area of 868.192 m2, the total rainfall potential that can be harvested is 2.388.129,13 m3. On Golf Island there are 8 reservoirs with a maximum capacity of 215.507 m3, based on the results of the analysis, the reservoir can accommodate water to meet domestic water needs of 180 l/person/day and non-domestic needs of 25% of domestic needs throughout the year. In extreme conditions, the flood discharge value with a return period of 10 years is 61,60 m3/s, because the reservoir is used for harvesting rainwater, rain in extreme conditions is discharged into the sea with the help of a pump. It is planned that for a pump with a capacity of 5,5 m3/s as many as 6 units to discharge rainwater in extreme conditions, the pump produces a power of 428,95 KW/unit. With the application of a rainwater harvesting system on Golf Island, it can hold runoff water so that very little rainwater comes out through the area, which is a maximum of 8,5% per year. This rainwater harvesting method, it's considered very effective in utilizing rainwater as well as controlling floods or puddles that may occur.